Interpreting productivity growth in the new economy: Some agnostic notes - Erich Gundlach (Kiel Institute of World Economics (IfW), 2001)
The growth rate of total factor productivity seems to have increased recently, at least in the United States. Higher US productivity growth may justify higher stock market valuations than in the past and thus herald an emerging New Economy. However, the size of the estimated growth rate of total factor productivity depends on an assumption about the factor-augmenting properties of technological change. Simulations based on alternative properties of technological change produce a wide range of implied stock market valuations. As long as the rate of technological change cannot be observed directly, justifying the emergence of a New Economy with residual measures of total factor productivity growth will prove to be a futile exercise.
Keywords: O47; 330; technological change; total factor productivity growth; Produktivität; Wirtschaftswachstum; Arbeitsproduktivität; Technischer Fortschritt; Dekompositionsverfahren; Börsenkurs; Realzins; Kritik; Schätzung; Theorie; Welt